KONSTRUKSI PRESENTASI DIRI: STUDI PADA PRIA METROSEKSUAL DI INSTANSI PEMERINTAHAN - Dianita Wahyuningtyas (Jurnal Kawistara, 2017)
Urban modernization has affected the behavior of the people in it. Today, real phenomenon is the emergence of an urban men’s lifestyle who really cares about her physical appearance like women. Previously, this lifestyle initially seen as hegemony and monopoly media celebrities, now replicated by people in everyday appearance, including a group of men in certain professions. The phenomenon of the metrosexual man in the government bureaucracy becomes interesting to study which stereotypes that the government bureaucracy are closed and rigid culture. Construction self-presentation shows an overview of social identity and self esteem. This study used a qualitative descriptive exploratory approach through the case study method. With purposive sampling technique, researchers determined the study subjects according to general characteristics of the metrosexual men. Researchers conducted in-depth interviews on four informants metrosexual men in the Ministry of Finance with a different of profession, age, and status. The conclusion is informant’s lifestyle more positively oriented. They tend narcissism, tidy, fashionoriented and more consumptive. Through informan’s self-presentation, the results show that bodyguard professions more recently adopting the metrosexual lifestyle than any other professions. Based on the characteristics of the AIO, the results showed four types of metrosexual men lifestyle, among other types of sport, trendy, automotive and artistic. Motivation of informan’s behavior in line with the general metrosexual cycle. Diverse motives behind the desire informant lifestyle look attractive especially to the opposite sex, work demands, and also increase comfort in social interaction. However, the phases of the metrosexual were experienced by the informants ‘non-linear’ as in general. While associated with the consumption patterns, the entire informants have high interest to the consumer. The findings showed that all informants included in the category of impulsive buyers who think rationally and selectively.